Dinamika Kota Dalam Persepsi Seniman: Relief ‘Jogja On The Move’ Di Bandara Internasional Yogyakarta Karya Entang Wiharso - Witjaksono, Bambang (Institut Seni Indonesia Yogyakarta, 2025)
This research describes the dynamics of the city of Yogyakarta/Jogja through a work of art in the form of a relief entitled 'Jogja On the Move' by Entang Wiharso in the departure boarding lounge of Yogyakarta International Airport (YIA). In this study, the researcher makes a frame based on the study of artworks towards the development of dynamics that occur in the city of Jogja. Aspects of historical depictions and sites in the city of Jogja are included in the dynamics of its development. The method used is descriptive analytical qualitative in describing artworks towards the dynamics of the city of Jogja found when observing relief artworks in the YIA departure lounge. This research describes the visualization of works of art, especially in terms of the meaning of symbols and texts. From the researcher's observation of the artworks, it was found that the relief artwork entitled 'Jogja On the Move' is an experience, observation, hope and criticism from the artist Entang Wiharso towards the tough tug-of-war between tradition and modernity in the city of Jogja. This can be used as an example to raise public awareness of the need for readiness in navigating the changes or dynamics of a city.Penelitian ini mendeskripsikan dinamika kota Yogyakarta/Jogja melalui karya seni rupa berupa relief berjudul ‘Jogja On the Move’ karya Entang Wiharso di ruang tunggu keberangkatan Bandara Internasional Yogyakarta (Yogyakarta International Airport/YIA). Dalam penelitian ini, peneliti membuat bingkai berdasarkan kajian karya seni terhadap perkembangan dinamika yang terjadi di Jogja. Aspek penggambaran sejarah serta situs di Jogja tercakup dalam dinamika perkembangannya. Metode yang digunakan adalah deskriptif analitis bersifat kualitatif dalam menggambarkan karya seni rupa terhadap dinamika Jogja yang ditemukan saat melakukan pengamatan pada karya seni relief di ruang tunggu keberangkatan YIA. Penelitian ini menjabarkan visualisasi karya seni rupa terutama secara pemaknaan simbol dan teks. Dari pengamatan peneliti terhadap karya yang dihasilkan, ditemukan bahwa karya relief berjudul ‘Jogja On the Move’ merupakan pengalaman, pengamatan, harapan serta kritik dari seniman Entang Wiharso terhadap tarik ulur yang alot antara tradisi dan modernitas di Jogja. Hal ini dapat dijadikan contoh untuk menggugah kesadaran masyarakat bahwa perlu kesiapan dalam mengarungi perubahan atau dinamika sebuah kota.